Analisis dan Perancangan Aplikasi Berbasis Web untuk Pengajuan Topik Tugas Akhir - Meliana Christianti Johan; Erico Darmawan Handoyo; Sulaeman Santoso; Christian Chastro (Maranatha University Press, 2021)
Maranatha Christian University Bandung is one of the universities in Indonesia that has a Faculty of Information Technology. In the Faculty of Information Technology there is an Informatics Engineering Study Program. The thing that underlies this research is that there is currently no integration between the Practical Work courses and the Final Project courses. For this reason, this research will try to analyze and design one application that will be carried out. The hope of this research is to help the process of submitting practical work topics and students' final assignments so that data is integrated and the recording process is better because it uses a web-based application. This application is a web-based application so it can be used anytime and anywhere.